2017
DOI: 10.12934/jkpmhn.2017.26.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Emotional Labor, Nursing Work Environment, and Self-efficacy on Happiness Index among National Psychiatric Hospital Nurses in Korea

Abstract: Purpose: This study was conducted to identify emotional labor, nursing work environment, self-efficacy and happiness index and address factors associated with happiness index to provide basic resources for national psychiatric hospital nurses' happiness at work. Methods: Participants were 249 nurses working in 5 national psychiatric hospitals. They participated in the survey and data were collected from May 16 to July 30, 2016. Data were analysed using SPSS/WIN 22.0. Results: Mean scores were nurses' emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, this score was lower than that reported in a previous study targeting hospital nurses (3.90) ( 23 ), which may reflect the difference between general and psychiatric nursing. Other previous studies ( 24 , 25 ) have reported that psychiatric nurses often engage in emotional labor while on duty; however, they are also constantly engaged in mental health education and training that they can use as therapeutic tools for themselves, indicating that they may have a better ability to regulate their emotions. Another study also reported that nurses with high emotional intelligence are more effective in applying emotional regulation strategies ( 25 ).…”
Section: Discussionmentioning
confidence: 91%
“…However, this score was lower than that reported in a previous study targeting hospital nurses (3.90) ( 23 ), which may reflect the difference between general and psychiatric nursing. Other previous studies ( 24 , 25 ) have reported that psychiatric nurses often engage in emotional labor while on duty; however, they are also constantly engaged in mental health education and training that they can use as therapeutic tools for themselves, indicating that they may have a better ability to regulate their emotions. Another study also reported that nurses with high emotional intelligence are more effective in applying emotional regulation strategies ( 25 ).…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the happiness index was also influenced by self-efficacy, work environment, and emotional affairs. [ 16 ] The results of the study by Villotti et al revealed that, in a general working environment, social support provides the grounds for enhancing the perceived productivity through reducing the internal concern level and raising the level of trust. In this study, during the multilevel (serial) multiple mediator test, an indirect effect of high specific social support of the workplace on job productivity through reducing both internal motivation and occupational long-term self-efficacy was noticeable.…”
Section: Discussionmentioning
confidence: 99%